Power Flow Solution Using Impedance Parameters - Jegatheesan, Ramiah; Mohd Nor, Nursyarizal; Romlie, Mohd Fakhizan (2008)
Bus admittance matrix is invariably used for the power flow solution. In this paper, power flow analysis that makes use of only impedance parameters is presented. The inverse of Jacobian matrix is obtained very easily by doing simple mathematical operations on the bus impedance matrix of the transmission network. This constant matrix is used to update the solution in each iteration. The proposed method is tested on IEEE systems and found to give good results. As compared to the Fast Decoupled Power Flow method, the proposed one takes lesser number of iterations to get the exact solution. The proposed power flow method can be extended to solve power flow problem associated with large power systems, using piecewise solution technique.